2009
DOI: 10.1074/jbc.m109.047753
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Liver X Receptor Prevents Lipopolysaccharide-induced Lung Injury

Abstract: The liver X receptors (LXRs) have been known as sterol sensors that impact cholesterol and lipid homeostasis, as well as inflammation. Although the hepatic functions of LXRs are well documented, whether and how LXRs play a pathophysiological role in the lung remain largely unknown. Here we show that LXR␣ and LXR␤ are expressed in both type I and type II mouse lung epithelial cells, as well as in human lung cancer cells. To study the role of LXR␣ in vivo including the pulmonary function of this LXR isoform, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 55 publications
(49 reference statements)
4
41
0
1
Order By: Relevance
“…LXR activation by synthetic agonists leads to decreased neutrophil recruitment and increased bacterial burden, indicating that LXR activation balance contributes to host immune defense (46). Recent studies also suggest that LXR agonists show therapeutic promise in treating lung disorders such as dyslipidemia and asthma (43,47,48). Furthermore, our data show that O 3 exposure of LXR␣ Ϫ/Ϫ mice results in enhanced pro-inflammatory response, indicating the importance of normal LXR␣ activity to regulate O 3 -induced inflammation (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…LXR activation by synthetic agonists leads to decreased neutrophil recruitment and increased bacterial burden, indicating that LXR activation balance contributes to host immune defense (46). Recent studies also suggest that LXR agonists show therapeutic promise in treating lung disorders such as dyslipidemia and asthma (43,47,48). Furthermore, our data show that O 3 exposure of LXR␣ Ϫ/Ϫ mice results in enhanced pro-inflammatory response, indicating the importance of normal LXR␣ activity to regulate O 3 -induced inflammation (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Recent studies have revealed important roles for cholesterol regulators on pulmonary immune responses to the lung injury and infection [29][30][31][32]. The exact pathophysiological mechanisms of cholesterol in severe illness and sepsis have never been fully understood.…”
Section: Discussionmentioning
confidence: 98%
“…A protective role of LXR agonists against LPS-mediated tissue injury has been demonstrated in vivo in the liver and the lung [50,51]. LXR is also able to regulate the expression of proteins potentially involved in LPS detoxification such as PLTP and CETP [52,53].…”
Section: Towards a New Strategy For Prevention And Treatment Of Endotmentioning
confidence: 97%